The Films of Ingmar Bergman - Hubner, L. author. aut Link
VI, 189 p.
Keywords: Laura Hubner is one of the first critics to analyse the elements of 'illusion' in key films by Bergman and relate these to cultural and artistic influences on his creative output, the phenomenon of Bergman as 'art film' director, and debates about modernism, postmodernism and emerging feminist discourses on gender and multiplicity.